Factors affecting memorability of service failures: A longitudinal analysis - Kim, Jong; Jang, S. (Emerald Group Publishing Limited, 2016)
Purpose – This study aims to identify the influences that lead to better memorability of a service by focusing on type of service failure, recovery condition and frequency of occurring. Design/methodology/approach – This study used a quasi-experimental design in which customers answered questions about a restaurant they had recently patronized and then evaluated experimentally generated failure and recovery scenarios. Two follow-up contacts were made (by phone and e-mail) to assess their memory of the imagined service failures stimulated by the scenarios. Participants were asked how clearly and vividly they could recollect the service failure and to indicate their behavioral intentions at the time of recall. Findings – The type of service failure and the subsequent recovery efforts significantly affect whether negative service experiences are memorable. Specifically, individuals showed a higher likelihood of vividly recalling a core service failure than an interactional one. Moreover, service recoveries were found to be helpful in decreasing the memorability of service failures, and that they were effective in decreasing the resulting negative customer behavioral intentions (i.e. switching behaviors and negative word-of-mouth). However, frequently occurred service failures did not significantly influence the memorability of the failures. Practical implications – The current study suggested what characteristics of service failures and situations lead to strong memorability and significantly affect future behavior. Thus, the findings provide important implications for avoiding and handling the failures that trigger strong memorability. Originality/value – Previous researchers have emphasized on the importance and urgency of preventing critical service failures. However, it is still unclear what type of service failures and/or factors are critical ones. The current study expands the knowledge by incorporating service failures with memory and investigates the characteristics of memorable service failures, which are likely to be remembered more vividly.